A blended continuum damage and fracture mechanics method for progressive damage analysis of composite structures using XFEM. (15th January 2018) - van Dongen, Björn; van Oostrum, Alexander; Zarouchas, Dimitrios
Abstract: Progressive damage analysis of composite structures remains problematic, holding back the full potential of these materials. Widely used continuum damage models feature a heuristical stiffness reduction to reflect damage, resulting in an unrealistic representation of damage patterns. To the end of a more realistic failure representation, this paper proposes a blended methodology for progressive damage analysis of such structures implemented in ABAQUS, combining continuum damage models with a more physically based approach from a fracture mechanics perspective. Matrix cracks are modelled through the eXtended Finite Element Method and delaminations through a cohesive zone model. Validation of the blend on an experimental campaign of open-hole tensile tests shows remarkable predictive capability, in good conformance to experimental failure loads, digital image correlation and acoustic emission measurements - particularly yielding more realistic damage patterns than state-of-the-art continuum damage model implementations.